Effect of plant spacing and pest controls of Spodoptera exigua on shallots in Majalengka Regency, West Java - Nurawan Agus; Hamdani Kiki Kusyaeri (E3S Web of Conferences, 2021)
This study examines the spacing and control of Spodoptera exigua pests on shallot plants in West Java. The research was conducted in Payung Village, Rajagaluh District, Majalengka Regency, West Java from September to November 2018. The study used a randomized complete block design with a total of four treatments and six replications. The treatments consisted of 1) spacing 15 x 20 cm + traps, 2) spacing 18 x 20 cm + traps, 3) spacing 20 x 20 cm + traps, and 4) spacing 20 x 20 cm + chemical. Data were analysed using the F test and followed by the Duncan test at the 95% confidence level. The results showed that the treatment of 18 x 20 cm spacing + traps resulted in the highest productivity of shallots compared to other treatments, namely 13.5 tons per hectare. The use of sex pheromone traps was more effective in controlling S. exigua pests than light traps and yellow traps.